Analisis pemanfaatan perpustakaan dalam meningkatkan minat baca bagi siswa kelas 4 sekolah dasar - Aida Putri Sukmaranti; Hadi Mulyono; Siti Istiyati (Universitas Sebelas Maret, 2021)
This research aims to explain the function of the library, the availability of library book collections, and library management in increasing reading interest for grade 4 students of SD Negeri Soropadan Surakarta. This research is expected to provide positive input to the school in utilizing the school library, as well as efforts to improve the quality of the school library and students' reading interests. This research is qualitative research with descriptive qualitative research method. Data collection is done by observation techniques, interviews, questionnaires, and documentation studies. Data sources are obtained from principals, grade IV teachers, librarians, and students. Validity of data using source triangulation. Data analysis using Miles and Huberman's interactive analytics model. The results showed that the educational function, informative function, and recreational function of the SD Negeri Soropadan library were felt by more than 50% of the students. Judging from the collection of books that are in accordance with the curriculum, thus helping students' learning. The library is used as a place for students to learn. The availability of adequate books, various types and providing books that are entertaining for students. The availability of book collections in various types and classified libraries. Collection of books oriented and relevant according to the needs of students. The arrangement and arrangement of library materials for students is already interesting. Procurement and development only relies on assistance from the government and other parties. Library management is carried out by teachers not professionals. Library services, such as circulation services, reference services, and reading room services are already running. So it was concluded that the use of the SD Negeri Soropadan library including functions, availability of collections, and management was not optimal in increasing students' reading interest.